Объяснение:
a)x²+6x+8
Д=6²–4*1*8=36–32=4
х(1)=
х(2)=
б)x²-8x+15
Д=(–8)²–4*1*15=64–60=4
в)x²+3x+2
Д=3²–4*1*2=9–8=1
г)x²-5x+6
Д=(–5)²–4*1*6=25–24=1
Объяснение:
a)x²+6x+8
Д=6²–4*1*8=36–32=4
х(1)=![\frac{ - 6 + \sqrt{4} }{2 \times 1} = \frac{ - 6 + 2}{2} = \frac{ - 4}{2} = - 2](/tpl/images/1106/1450/ad335.png)
х(2)=![\frac{ - 6 - \sqrt{4} }{2 \times 1} = \frac{ - 8}{2} = - 4](/tpl/images/1106/1450/c3907.png)
б)x²-8x+15
Д=(–8)²–4*1*15=64–60=4
х(1)=![\frac{8 + \sqrt{4} }{2 \times 1} = \frac{8 + 2}{2} = 5](/tpl/images/1106/1450/8d92f.png)
х(2)=![\frac{8 - \sqrt{4} }{2 \times 1} = \frac{8 - 2}{2} = 3](/tpl/images/1106/1450/8f1b0.png)
в)x²+3x+2
Д=3²–4*1*2=9–8=1
х(1)=![\frac{ - 3 + \sqrt{1} }{2 \times 1} = \frac{ - 3 + 1}{2} = \frac{ - 2}{2} = - 1](/tpl/images/1106/1450/d1df7.png)
х(2)=![\frac{ - 3 - \sqrt{1} }{2 \times 1} = \frac{ - 4}{2} = - 2](/tpl/images/1106/1450/9fae2.png)
г)x²-5x+6
Д=(–5)²–4*1*6=25–24=1
х(1)=![\frac{ 5 + \sqrt{1} }{2 \times 1} = \frac{6}{2} = 3](/tpl/images/1106/1450/c872a.png)
х(2)=![\frac{5 - \sqrt{1} }{2 \times 1} = \frac{4}{2} = 2](/tpl/images/1106/1450/9eba4.png)